Patterns of serial rib fractures after blunt chest trauma: An analysis of 380 cases. - Christian Liebsch; Tina Seiffert; Markus Vlcek; Meinrad Beer; Markus Huber-Lang; Hans-Joachim Wilke (PLoS ONE)
Rib fractures represent the most common bone fracture, occurring in 10-20% of all blunt trauma patients and leading to concomitant injuries of the inner organs in severe cases. The purpose of this study was to identify specific serial rib fracture patterns after blunt chest trauma. 380 serial rib fracture cases were investigated. Fractures were assigned to five different locations within the transverse plane. Rib level, fracture type, and dislocation grades were recorded and related to the cause of accident. In total, 3735 rib fractures were identified (9.8 per patient). 54% of the rib fractures were detected on the left thorax. Rib fracture distribution exhibited a hotspot at rib levels 4 to 7 in the lateral and posterolateral segments. On average, most rib fractures occurred in crush/burying injuries (15.8, n = 13) and pedestrian accidents (12.8, n = 13), least in car/truck accidents (8.9, n = 75). In the car/truck accident group, 47% of all rib fractures were in the lateral segment, in case of frontal collision (n = 24) even 60%. Fall injuries (n = 141) entailed mostly posterolateral rib fractures (35%). In case of falls >3 m (n = 45), 48% more rib fractures were detected on the left thorax. In cardiopulmonary resuscitation related serial rib fractures (n = 33), 70% of all rib fractures were located anterolaterally. Infractions were the most observed fracture type (44%), followed by oblique (25%) and transverse (18%) fractures, while 46% of all rib fractures were dislocated (15% ≥ rib width). Serial rib fractures showed distinct fracture patterns depending on the cause of accident. When developing a serial rib fracture classification system, data regarding patterns, fracture types, dislocation grades, and associated fractures should be included.